Teachers’ Roles in Fostering Environmental Awareness in Early Childhood Education: A Qualitative Study - Fitriyah Fitriyah; Imelda Indah Lestari; Zineb El Atmani (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: Escalating ecological challenges caused by unsustainable human activities have intensified the global urgency to cultivate environmental awareness from an early age. Early Childhood Education (ECE) plays a strategic role in shaping pro-environmental values, attitudes, and behaviors. However, empirical studies examining how teachers enact environmental education practices in local early childhood settings, particularly in underrepresented regions of Indonesia, remain limited. Aims and scope of paper: This study aims to explore the role of teachers in fostering environmental awareness among young children by examining their roles as role models and facilitators, identifying instructional strategies employed in daily learning activities, and analyzing supporting and inhibiting factors influencing the development of environmentally responsible character in early childhood education. Methods: A qualitative descriptive approach was employed to gain an in-depth understanding of naturalistic practices in an early childhood education setting in Indonesia. Data were collected through direct classroom observations, in-depth interviews with teachers, the school principal, and parents, as well as documentation analysis. Data analysis was conducted iteratively through data reduction, data display, and conclusion drawing/verification to ensure analytical rigor and credibility. Results: The findings reveal that teachers play a central role as moral exemplars in internalizing environmental values, as evidenced by children’s active participation in routine environmental activities. Instructional strategies included concrete and experiential practices such as watering plants, waste sorting, and the use of visual learning media, which significantly enhanced children’s engagement and sense of environmental responsibility. Supporting factors included structured habituation and adequate school facilities, while challenges were mainly related to inconsistencies in individualized guidance. Contribution: This study contributes to the international early childhood education literature by providing empirical evidence that environmental education is most effective when embedded holistically within school culture and grounded in teacher role-modelling practices. The findings underscore the importance of sustained collaboration between teachers and parents to ensure the continuity and long-term impact of pro-environmental behaviors in early childhood.